Pengaruh Modal Dan Lama Usaha Terhadap Pendapatan Pedagang Dalam Perspektif Bisnis Syariah (Studi Pada Pedagang Pasar Sentral Watampone) - St Habibah; Sri Astuti (Institut Agama Islam Negeri (IAIN) Bone, 2018)
This study aims to determine whether capital and duration of business have a simultaneous influence on the income of traders in sharia business in the Makassar Central Market and how much influence the capital and business duration have on the income of traders in sharia business at Makassar Central Market. The Capital Research Results significantly affect the income of the central market trader Watampone (t = 3.259). This shows that the greater the capital of a business can affect the development of merchant business so that it can increase the income of traders. The T statistic is positive (t = 3.259), meaning that there is a significant capital relationship in increasing the income of Central Market Watampone traders, in this study that capital is the most important thing in doing business, including trading.